The Effect of Open Tourism Space on Regional Development Through Supply Chain Management in Panatapan Danau Toba Area Simalungun, Indonesia - Jumadil Saputra; Muhammad Ade Kurnia Harahap; Sirojuzilam Sirojuzilam; R. Hamdani Harahap; Beny O. Y. Marpaung (International Journal of Supply Chain Management, 2019)
This study aims to analyze the influence of open space tourism on regional development, both through visitor satisfaction, image or destination image, and visitor interest and loyalty (intention and loyalty). This research was conducted in several Panatapan spots as open-air tourist spaces in Simalungun Regency, with a total of 313 respondents. The data sources used are primary and secondary data obtained through questionnaires and documentation. The data analysis used in this study uses Structural Equation Modeling (SEM) with SmartPLS 3.0 tools. The results of the study show the importance of developing open space in an effort to build a tourism image, tourist satisfaction, visitor interest and loyalty, in supporting regional development in Simalungun District.